Kitten Construction Company : meet the house kittens - Green, John Patrick, 1975- (First Second, 2018)
Marmalade, a trained architect who also happens to be an adorable kitten, finds allies in other construction-trade cats when her plans for the new mayor's mansion are rejected by the city planner.